The impact of acetate metabolism on yeast fermentative performance and wine quality: reduction of volatile acidity of grape musts and wines - Moura, A. Vilela (2011)
Acetic acid is the main component of the volatile acidity of grape musts and wines. It can be formed as a byproduct of alcoholic fermentation or as a product of the metabolism of acetic and lactic acid bacteria, which can metabolize residual sugars to increase volatile acidity. Acetic acid has a negative impact on yeast fermentative performance and affects the quality of certain types of wine when present above a given concentration. In this minireview, we present an overview of fermentation conditions and grape-must composition favoring acetic acid formation, as well the metabolic pathways leading to its formation and degradation by yeast. The negative effect of acetic acid on the fermentative performance of Saccharomyces cerevisiae will also be covered, including its role as a physiological inducer of apoptosis. Finally, currently available wine deacidification processes and new proposed solutions based on zymological deacidification by select S. cerevisiae strains will be discussed.